Attention‐deficit/hyperactivity disorder without comorbidity is associated with distinct atypical patterns of cerebral microstructural development. Issue 5 (1st August 2013) - Adisetiyo, Vitria; Tabesh, Ali; Di Martino, Adriana; Falangola, Maria F.; Castellanos, Francisco X.; Jensen, Jens H.; Helpern, Joseph A.
Abstract Differential core symptoms and treatment responses are associated with the pure versus comorbid forms of attention‐deficit/hyperactivity disorder (ADHD). However, comorbidity has largely been unaccounted for in neuroimaging studies of ADHD. We used diffusional kurtosis imaging to investigate gray matter (GM) and white matter (WM) microstructure of children and adolescents with ADHD (n = 22) compared to typically developing controls (TDC, n = 27) and examined whether differing developmental patterns are related to comorbidity. The ADHD group (ADHD‐mixed) consisted of subgroups with and without comorbidity (ADHD‐comorbid, n = 11; ADHD‐pure, n = 11, respectively). Age‐related changes and group differences in cerebral microstructure of the ADHD‐mixed group and each ADHD subgroup were compared to TDC. Whole‐brain voxel‐based analyses with mean kurtosis (MK) and mean diffusivity (MD) metrics were conducted to probe GM and WM. Tract‐based spatial statistics analyses of WM were performed with MK, MD, fractional anisotropy, and directional (axial, radial) kurtosis and diffusivity metrics. ADHD‐pure patients lacked significant age‐related changes in GM and WM microstructure that were observed globally in TDC and had significantly greater WM microstructural complexity than TDC in bilateral frontal and parietal lobes, insula, corpus callosum, and right external and internal capsules. Including ADHD patients with diverse comorbidities in analyses masked these findings. A distinct atypical age‐related trajectory and aberrant regional differences in brain microstructure were detected in ADHD without comorbidity. Our results suggest that different phenotypic manifestations of ADHD, defined by the presence or absence of comorbidity, differ in cerebral microstructural markers. Hum Brain Mapp 35:2148–2162, 2014. © 2013 Wiley Periodicals, Inc.